(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Interleaved converters are used in many different conversion systems involving various topologies and are related to different fields of application due its advantages over single-phase converters. Such advantages include reduced current in switching devices and passive elements, reduced output current ripple, and so on. Reductions in size and costs of magnetic components and inductors current ripple can be achieved by an integration of magnetics. In this paper application of 2-phase coupled inductor designed in convenient way by using commercially manufactured coil formers and ferrite cores is analyzed to developed 4-phase interleaved DC-DC converter. Different structures of the coupled inductor for 4 phases is studied. The steady state phase and output current ripple in buck mode of the interleaving magnetic integrated bidirectional DC-DC converter is simulated. The necessary count of inductors for selected topology are manufactured and placed on the PCB board.